Penyuluhan Manajemen Seleksi Dan Pencatatan Data Ternak Sapi Pada Kelompok Ternak Iwaq Jaya Farm Di Desa Jango Kecamatan Janapria Kabupaten Lombok Tengah - Eva Amalia Pertiwi; Tapaul Rozi; Muhsinin; Maskur (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Bali cattle are an endemic Indonesian germplasm known for high reproductive potential and adaptability; however, their genetic quality at the smallholder farmer level has tended to decline due to improper selection management. This community service activity aimed to educate the "Iwaq Jaya Farm" livestock group in Janapria District, Central Lombok, regarding the importance of livestock selection and recording systems. The methods employed included surveys, observations, and discussion-based presentations. Results indicated that farmers still implement traditional rearing systems with a small ownership scale of 3–6 head. Education focused on selection techniques based on qualitative and quantitative traits (body weight and body dimensions), as well as basic recording techniques for lineage and feed. Through this assistance, farmers are expected to perform independent selection using simple measuring tools to improve genetic quality and livestock productivity in the future.